2021
DOI: 10.3390/ijerph18094630
|View full text |Cite
|
Sign up to set email alerts
|

Relative Handgrip Strength as Marker of Cardiometabolic Risk in Women with Systemic Lupus Erythematosus

Abstract: This study aimed to examine the association of relative handgrip strength (rHGS) with cardiometabolic disease risk factors in women with systemic lupus erythematosus (SLE). Methods: Seventy-seven women with SLE (mean age 43.2, SD 13.8) and clinical stability during the previous six months were included. Handgrip strength was assessed with a digital dynamometer and rHGS was defined as absolute handgrip strength (aHGS) divided by body mass index (BMI). We measured blood pressure, markers of lipid and glucose met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Our results revealed that there are certain measures of burden that have been poorly evaluated in recent literature, such as the burden of treatment, disability, health care utilization, work participation, and, clearly, economic burden [ 13 , 28 ]. Most studies to date that have attempted to assess the impact of obesity and diabetes on the health outcomes of SLE patients have a cross-sectional design, so causality cannot be inferred [ 15 , 19 , 29 , 30 , 31 ]. This has determined that the role of obesity and diabetes in SLE remains poorly understood [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed that there are certain measures of burden that have been poorly evaluated in recent literature, such as the burden of treatment, disability, health care utilization, work participation, and, clearly, economic burden [ 13 , 28 ]. Most studies to date that have attempted to assess the impact of obesity and diabetes on the health outcomes of SLE patients have a cross-sectional design, so causality cannot be inferred [ 15 , 19 , 29 , 30 , 31 ]. This has determined that the role of obesity and diabetes in SLE remains poorly understood [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For optimal prevention and treatment of atherosclerosis, it is not self-evident that women and men show similar responses to risk factors or treatment; therefore, studies must present results according to sex. Whether the threat and risk factors of premature atherosclerosis in women with SLE are generalized to male patients is unknown [ 3 , 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Weaker hand grip strength has been observed in adults with SLE relative to non-SLE comparators, 5 and weaker hand grip is associated with higher cardiometabolic risk when adjusted for body mass index (BMI). 6 …”
Section: Introductionmentioning
confidence: 99%
“…In general population, higher levels of muscle strength have shown to be related to a lower risk of developing cardiovascular disease [ 22 ], type 2 diabetes [ 20 ], fragility [ 23 ] and mortality [ 24 ]. Specifically, handgrip strength (HGS), and HGS relative to the body mass index (BMI), have been proposed as highly relevant health indicators in different populations, such as young and older adults [ 25 ], adult males [ 26 ], aging adults [ 27 ], women with systemic lupus erythematosus [ 28 ], and women with fibromyalgia [ 29 ]. HGS and relative HGS (rHGS) have also been proposed as a cardiometabolic risk predictor in children and adolescents [ 30 ] and in middle-aged and older people [ 31 , 32 ], and as an all-cause [ 33 , 34 , 35 ] and cancer [ 36 ] mortality predictor, allowing to obtain useful information from a simple, quick, and very low-cost assessment.…”
Section: Introductionmentioning
confidence: 99%
“…RHGS is a good indicator of general health in different populations. For instance, higher levels of rHGS are associated with greater mobility in older adults [ 46 , 47 ], better cardiovascular health in obese women [ 48 ], lower prevalence of metabolic syndrome in adults [ 49 ], lower prevalence of osteoporosis in women [ 50 ], lower cardiometabolic risk in women with systemic lupus erythematosus [ 28 ], and lower risk of depressive mood in women [ 39 ]. Therefore, we speculated that higher rHGS would be related to better self-reported physical function and HRQoL in female breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%